Carbon nanotube composite, method for making the same, and electrochemical capacitor using the same - ZHOU RUI-FENG; JIANG KAI-LI; FAN SHOU-SHAN; LIU KAI; SUN YING-HUI (2012)
A carbon nanotube composite includes a free-standing carbon nanotube structure and an amount of reinforcements. The free-standing carbon nanotube structure includes an amount of carbon nanotubes. The reinforcements are located on the carbon nanotubes and combining the carbon nanotubes together.